Sarcopenia in Metastatic Renal Cell Carcinoma Patients Treated with Cabozantinib - Buchler, Tomas; Kopecka, Marie; Zemankova, Anezka; Wiesnerová, Markéta; Streckova, Eva; Rozsypalova, Aneta; Melichar, Bohuslav; Poprach, Alexandr; Richter, Igor (Targeted oncology, 2020)
BACKGROUND: Sarcopenia is common in advanced cancer and correlates with poor performance status, increased risk of treatment-related toxicity, and shortened survival. Inhibitors of the vascular endothelial growth factor pathway have been associated with development or deterioration of sarcopenia. OBJECTIVE: To assess the prevalence and impact of sarcopenia on survival in patients with metastatic renal cell carcinoma (mRCC) treated with cabozantinib, a novel, highly potent multikinase inhibitor. PATIENTS AND METHODS: Patients treated with cabozantinib for mRCC progressing on other targeted therapies with available computed tomography (CT) scans acquired at the time of initiation of cabozantinib and on the first restaging were evaluated retrospectively. Muscle mass was assessed based on striated muscle area at the level of the third lumbar vertebra. RESULTS: The median muscle mass index at CT1 and CT2 was 52.2 cm2/m2 (range 33.0-69.2 cm2/m2) and 49.1 cm2/m2 (range 33.1-68.2 cm2/m2), respectively. Sarcopenia was initially present in 13 (44.8%) patients. The mean muscle mass change between CT1 and CT2 was - 2.2 cm2/m2 (range - 10.1 to + 4.8cm2/m2). Six-month progression-free survival (PFS) was significantly shorter in patients with at least 10% muscle loss, reaching 50% (95% CI 9.9-90) versus 79.8% (95% CI 62.1-90.6) in others (p = 0.022). The presence of initial sarcopenia was not associated with grade 3-4 toxicity, which was reported in six (46.2%) and seven (46.7%) patients with and without sarcopenia, respectively. CONCLUSIONS: Significant and early skeletal muscle loss occurs during treatment with cabozantinib in a high proportion of patients and is associated with poor PFS.
Keywords: senioři; metastázy nádorů; Carcinoma, Renal Cell; Middle Aged; mužské pohlaví; Pyridines; pyridiny; karcinom z renálních buněk; Adult; Sarcopenia; Neoplasm Metastasis; ženské pohlaví; Humans; lidé středního věku; anilidy; sarkopenie; dospělí; Female; Aged; Anilides; lidé; Male